Total Quality Management as a Mechanism for Enhancing Job Empowerment: An Analytical Study in the Services Sector - Salah Ahmed Yousuf Salim (Journal of Scientific and Human Dimensions, 2026)
This study aims to explore the dialectical and complementary relationship between Total Quality Management (TQM) practices and employee empowerment in service sector organizations. The study is based on the premise that the human dimension of TQM is the primary driver for creating an empowering work environment that transcends rigid procedural frameworks. The research adopted a descriptive-analytical approach by reviewing contemporary literature and deconstructing theoretical models linking the two variables. The study concluded that quality principles, particularly supportive leadership and teamwork, act as structural platforms that grant employees autonomy and the ability to influence. The research also developed a proposed conceptual model that illustrates the pathways for the impact of quality to translate into psychological and structural empowerment, thus contributing to bridging the knowledge gap regarding how to transform a "quality culture" into a sustainable "empowering behavior."
Keywords: Quality Management (TQM); Employee Empowerment; Service Sector; Transformational Leadership; Job Satisfaction; Organizational Performance